Negotiation: types and ethical issues - Eishan Jan, Mohammad Naqib; Ahmad, Muhamad Hassan (CLJ Publication, 2020)
Negotiation is an alternative and yet peaceful means of resolving a dispute, which can be utilised by people or entities to settle their differences through compromise or agreement that would allow the parties to continue to maintain their mutually beneficial relationship after the resolution of their differences. Negotiation is a non-adjudicative, flexible, informal and confidential method that may be conducted bilaterally or multilaterally. An effective negotiation necessitates observance of certain ethical values by the negotiators including honesty, trust, fairness, etc., that would enable them to resolve their differences justly and fairly, and at the same time make sure that the relationship between the parties continues to flourish. The scope of this chapter does not cover all aspects of negotiation as it focuses only on the types of negotiation and its ethics.